Shedding new light on the context and temporality of Iberian warrior stelae: The Cañaveral de León 2 Stela and Las Capellanías burial complex (Huelva, SW Spain) - Leonardo García Sanjuán; Timoteo Rivera-Jiménez; Marta Díaz-Guardamino; David Wheatley; José Antonio Lozano Rodríguez; Teodosio Donaire Romero; Antonio César González-García; Raquel Montero Artús; José Ruiz Flores; Javier Bermejo Meléndez; Miguel Ángel Rogerio-Candelera; Johan Ling; et al. (PLoS ONE, 2025)
Iberian late prehistoric stelae stand out as a significant expression of European prehistoric art. For well over a hundred years, the context of use of the c. 300 Iberian stelae known to this date has been intensely discussed. This debate, however, was inherently flawed and limited in its scope, as almost all the available examples were found by chance, and no good-quality empirical evidence was available to understand their primary context. In this paper, we present the first conclusive scientific evidence demonstrating that Iberian late prehistoric stelae were used both as grave markers and landscape landmarks associated with pathways. This incontrovertible evidence stems from fieldwork undertaken in June 2022 and September 2023 at the site of Las Capellanías (Cañaveral de León, Huelva) in south-west Spain, including field walking, geophysics and excavation. The ground-breaking discoveries made at this remarkable site within barely a year reveal the contextual association of three different stelae to as many graves within the context of a large long-standing burial complex. Specifically, in this paper we study Stela #2 through a broad combination of methods ranging from geoarchaeology to luminescence dating and archaeoastronomy, as well as multiple digital visualization and remote sensing techniques. This multidisciplinary approach provides data that reveal multiple lines of evidence concerning the context and temporality of the stela, its manufacture and its graphic design. Altogether, this lays out a much needed and long-awaited reliable empirical base to understand where, when and how Iberian prehistoric stelae were used. “We hewed logs and built his pyre upon the tallest headland where it runs out above the sea: duly we made his funeral, bewailing him with bitter tears. After body and armour were quite burned away, we piled a mound over them and to crown it dragged up a monolith”, Homer, The Odyssey (London, Arcturus, 2021. Trans. by Alexander Pope). “As he spoke he began stripping the spoils from the son of Paeon, but Alexandrus husband of lovely Helen aimed an arrow at him, leaning against a pillar of the monument which men had raised to Ilus son of Dardanus, a ruler in days of old”, Homer, The Illiad (Project Gutenberg, 2022. Trans. by Samuel Butler).